HANDLING STRATEGY OF DAMAGE AND COST ESTIMATION OF SITUBONDO-BAJULMATI ROAD MAINTENANCE LINK.025 KM SBY 233+000 – 251+000 - Andini Wihenda Lafatza; Akhmad Hasanuddin; Anita Trisiana (Universitas Jember, 2020)
Pantura highway, especially on Situbondo-Bajulmati Link. 025 Km Sby 233+00-251+00 road section is one of the road section points that have a high activity every day so the road conditions are not good. Routine and periodical road maintenance was done by DPU Bina Marga and then the comparison of realization and the theory-based costs was found out by using the International Roughness Index (IRI) method. After that, an analysis of routine and periodical maintenance during 10 years plan age to know the lowest and efficient cost to the road maintenance was conducted. The realization and theory-based costs of routine maintenance have a difference of Rp107.526.929. The realization and theory-based costs of periodical maintenance have a difference of Rp953.520.843. The difference between the realization and theory-based costs required DPU Bina Marga to do a strategy of road damage. The results of the analysis for 10 years plan age with the calculated interest shows that the routine maintenance once a year was considered as effective to be conducted to minimize cost. Jalan Raya Pantura, tepatnya ruas Jalan Situbondo-Bajulmati Link. 025 Km Sby 233+00-251+00 merupakan salah satu titik ruas jalan yang memiliki aktivitas tinggi setiap harinya sehingga kondisi jalannya kurang baik. Pemeliharaan rutin dan berkala jalan dilakukan oleh DPU Bina Marga dan selanjutnya akan dicari perbandingan biaya realisasi dan biaya sesuai teori yang menggunakan metode International Roughness Index (IRI). Setelah itu dilakukan analisis pemeliharaan rutin dan berkala jalan selama umur rencana 10 tahun untuk mengetahui biaya yang paling murah dan efisien untuk pemeliharaan jalan. Biaya realisasi dan biaya sesuai teori pemeliharaan rutin memiliki selisih Rp107.526.929. Biaya realisasi dan biaya sesuai teori pemeliharaan berkala memiliki selisih Rp953.520.843. Adanya perbedaan antara biaya realisasi dan biaya secara teori mengharuskan pihak DPU Bina Marga melakukan suatu strategi penanganan kerusakan jalan.. Hasil analisis selama umur rencana 10 tahun dengan bunga yang telah diperhitungkan menunjukkan bahwa pemeliharaan rutin 1 tahun sekali dinilai lebih efektif dilakukan untuk meminimalisir pembengkakan biaya.